The Story of Me: The Underprotection of Autobiographical Speech - Sonja R. West (Washington University Law Review, 2006)
This Article begins the debate over the constitutional underprotection of autobiographical speech. While receiving significant historical, scientific, religious, and philosophical respect for centuries, the time-honored practice of talking about yourself has been ignored by legal scholars. A consequence of this oversight is that current free speech principles protect the autobiographies of the powerful but leave the stories of “ordinary” people vulnerable to challenge. Shifting attitudes about privacy combined with advanced technologies, meanwhile, have led to more people than ever before having both the desire and the means to tell their stories to a widespread audience. This Article argues that truthful autobiographical speech deserves heightened constitutional protection. An analysis applying the various goals of free speech protection to autobiographical speech establishes that it occupies an exceptional place in the public discourse—perhaps rivaled only by political speech. Autobiographical speech adds vital knowledge to the public debate while also preserving the essence of human autonomy. This Article concludes, therefore, that it is time for the law to recognize and to fully protect the freedom of autobiographical speech.
Keywords: Autobiographies; Freedom of speech; Right of publicity; Right of privacy